Inbred mouse strains differ in resistance to lethal Coccidioides immitis infection. - Kirkland, T N (1983)
Inbred strains of mice were infected intraperitoneally with Coccidioides immitis, and the mean lethal dose was determined after 28 days. DBA/2N mice had a mean lethal dose of greater than 10(5) arthroconidia, whereas BALB/cAnN, C57BL/6N, and C57L/J mice had a mean lethal dose of less than or equal to 10(3). Since both BALB/c and DBA/2 mice are the H-2d haplotype, resistance is not primarily determined by the major histocompatibility locus. Resistance was the dominant phenotype. The pattern of C. immitis-resistant strains does not correspond to the strain distribution of the lsh gene or to the pattern of resistance to Blastomyces dermatitidis or Cryptococcus neoformans. Both resistant and susceptible mice, however, could be successfully immunized with a killed spherule vaccine, and susceptible BALB/cAnN mice were protected from an otherwise lethal infection by prior immunization with an attenuated mutant of C. immitis. Despite the evidence that BALB/cAnN mice could respond to immunization, nonimmune mice did not control the later phase of intraabdominal infection as well as DBA/2N mice. Dissemination of C. immitis to the lung occurred frequently in BALB/cAnN but not in DBA/2N mice. This suggests that BALB/cAnN mice cannot mount an effective immune response to C. immitis during the course of infection.